Characterisation of dwelling electricity demand with reference to DCHP - Geslot, Olivier (Cranfield University, 2002)
The research relates to the introduction of dwelling micro combined heat and power to the domestic sector as a mean of improving the efficiency with which primary energy is used, and the economic efficiency of supplying electricity via the national grid. Such small generators may constitute Stirling engine or solid polymer fuel cells. This research is orientated towards the electrical demand side issues. The context is to maximise the feasibility of such technologies when the typical domestic consumer's heat demand varies significantly with season and the associated electrical power varies substantially every minute of the day. The main issue was to ensure that the system could effectively and economically satisfy a considerable proportion of the electricity demand the typical demand profile is very peaky by virtue of the way inhabitants behave at home and the design of domestic appliances. To derive the characteristic of dwelling electricity demand, a total of 45 dwellings were sampled, monitored and classified, in order to analyse the parameters influencing the shape, magnitude and duration of the profile data collected. A survey was issued to . complete the research regarding appliances time of use. Then a model was designed with an interface allowing dynamism. The research concluded there are attractive reasons for micro combined heat and power to be implemented in dwelling. It could save up to 15% of primary fuel. On an annual basis, and with the 15 dwelling data provided by British Gas, the average saving for a constant lkWe DCHP is determined to be £44.78, and the saving is increased to £124.61 for a system that would allows a tumdown from lkWe DCHP during winter to 500We DCHP during summer. Furthermore utility companies should be gaining from this introduction because peak power demand reduction on the grid should reduce costs.